Extending Integrated Pest Management to indigenous vegetables - James, B.; Godonou, I.; Atcha-Ahowé, C.; Glitho, I.; Vodouhe, S.; Ahanchédé, A.; Kooyman, C.; Goergen, Georg E. (International Society for Horticultural Science, 2007)
Leafy gboma (Solanum macrocarpon) and amaranths (Amaranthus sp.) are the two most important indigenous vegetables in the urban and peri-urban areas of Benin. IITA’s vegetable project has generated extensive baseline information on diversity, distribution and economic importance of pests of the crops; identified abuse and misuse of chemical pesticides in the vegetable sector; isolated suitable strains of entomopathogenic fungi as biopesticides against foliage feeders; and identified botanicals against root knot nematodes. Among 435 project-trained vegetable producers (30% women), 81 of them serve as community organizers to assist their colleagues incorporate research findings into vegetable production, increase local ownership and wider adoption of IPM options. Private-sector participation is required to assist move proven biologically-based IPM options from experimental to commercial level.